THE ROAD TO SERENITY: A HOLISTIC ANALYSIS OF AL-KINDI’S CONCEPT OF HAPPINESS AND ITS CONTRIBUTION TO MENTAL HEALTH IN THE MODERN ERA - Habibie, Alfiesyahrianta; Ali Farhan, Zinedine; Soleh, Achmad Khudori; Maharani, Farah Diba (State Islamic University of Datokarama Palu, 2025)
Al-Kindi's concept of happiness offers a synthesis of rational philosophy and Islamic spirituality that is highly relevant in the modern era. This study aims to explore Al-Kindi's concept of happiness philosophically and practically, by exploring the methods of achieving it and its relevance in facing the challenges of contemporary life. The method used was a qualitative library research approach to collect and analyze data from various sources. The results show that Al-Kindi places reason as the primary instrument for achieving true happiness. He emphasized the importance of self-control over desires and emotions, as well as closeness to God as the pinnacle of eternal happiness. His rational approach to overcoming grief, which bears similarities to Rational Emotive Behavior Therapy (REBT), proves the relevance of his thinking in the context of modern psychology. Thus, Al-Kindi's thinking not only enriches the treasury of Islamic philosophy but also provides psychospiritual solutions for building a meaningful and happiness.